Toward the decoration of Pt nanoparticles supported on carbon nanotubes with Fe oxides and its effect on the catalytic reaction - Guo, Zhen (2013)
Deposition of metallic oxides on noble metal catalysts improves their catalytic performance dramatically due to the highly active sites formed at the interface of two metals (nano-contact). In this work, Fe oxides were deposited on preformed Pt nanoparticles by using a novel microwave assisted polyol reduction method. The facile synthesis is performed in liquid phase at 438 K, which preserves the growth of large Pt nanoparticles and precludes the formation of Pt–Fe alloy. The Fe promoted Pt catalyst exhibited high activity (6340 h−1 in turnover frequency) and selectivity (89.1% for cinnamal alcohol) in the hydrogenation of cinnamaldehyde, which was attributed to the uniform distribution of Fe promoters on Pt surfaces. The characteristics of Fe oxides on Pt nanoparticles were identified by employing electrochemical analysis and X-ray photoelectron spectroscopy.